COVID-19 Impact on Regional Medical Campus Education: Student Perspectives - Obed Barkus (University of Minnesota Libraries Publishing, 2021)
Due to social distancing precautions and the desire to protect clinical learners, the COVID-19 pandemic forced medical schools everywhere to implement more distanced and virtualized learning in their educational curriculums. More specifically, at the University of Kansas School of Medicine-Salina, a regional medical campus, the impact of some of these changes were also seen and felt. The purpose of this study was to investigate the downstream effects of these curriculum changes from the perspectives and opinions of medical students attending a regional medical campus. To explore the study purpose, a mixed-methods, cross-sectional study that used an online survey with closed and open-ended questions was used. Additionally, because of unique curriculum characteristics depending on the year of the student, 1st and 2nd year students (phase I) were asked slightly different questions than students in their 3rd and 4th years (phase II). Closed-ended questions asked students about lecture experience, clinical learning development and time, study time, exam performance, collaborative learning experiences, and socialization/interactions with colleagues. Students answered in range of -3 to +3, negative numbers meaning a detrimental impact (or decrease in study time), and positive numbers being beneficial impact (or increase in study time). Open-ended questions asked students about improvements that could be made, unique class circumstances during the pandemic and any other relevant impact not covered in closed-ended questions. For phase I students, lecture experience, study time and exam performance resulted in no impact. However, collaborative learning and socialization with colleagues did result in a detrimental impact that was significant. For phase II learners, clinical skills development, time spent in clinical skills development and socialization with colleagues were detrimentally impacted. However, the amount of time spent on studying increased and exam performance benefited. These findings suggest that pandemic-related curriculum changes impact learners differently depending on the phase of medical they are in.